IMPROVING THE STUDENTS' READING COMPREHENSION USING DISCOVERY LEARNING AT ELEVENTH GRADE OF SMAN 1 BATUKLIANG - Gempar Nalar Jati; Siti Syafiatul Qomariyah; Sudirman (Journal of English Education and Literature, 2025)
Reading comprehension was identified as a crucial component of language acquisition, enabling students to derive meaning from written texts and apply this understanding to academic tasks. Despite its importance, observations conducted at SMAN 1 Batukliang revealed several persistent challenges. Students exhibited difficulties in pinpointing main ideas, understanding specific details, and comprehending overall text structures. These issues often led to reduced academic performance and lower engagement in learning activities.This study aimed to enhance students' reading comprehension through the implementation of the Discovery Learning method among eleventh-grade students at SMAN 1 Batukliang. Conducted using Classroom Action Research (CAR), the study included one cycles, each consisting of planning, action, observation, and reflection. Data collection involved pre-test and post-test assessments alongside observation sheets. The findings showed a significant improvement in students' reading comprehension skills. The pre-test average score of 62.34 rose to 82.03 in the post-test. These results demonstrated that Discovery Learning effectively fostered deeper understanding and engagement in reading activities.